Synthesis and antiviral activity of substituted quercetins - Thapa, Mahendra; Kim, Yunjeong; Desper, John; Chang, Kyeong-Ok; Hua, Duy H. (My University, 2012)
Influenza viruses are important pathogens that cause respiratory infections in humans and animals. In addition to vaccination, antiviral drugs against influenza virus play a significant role in controlling viral infections by reducing disease progression and virus transmission. Plant derived polyphenols are associated with antioxidant activity, anti-carcinogenic, and cardio- and neuro-protective actions. Some polyphenols, such as resveratrol and epigallocatechin gallate (EGCG), showed significant anti-influenza activity in vitro and/or in vivo. Recently we showed that quercetin and isoquercetin (quercetin-3-b-D-glucoside), a glucoside form of quercetin, significantly reduced the replication of influenza viruses in vitro and in vivo (isoquercetin). The antiviral effects of isoquercetin were greater than that of quercetin with lower IC50 values and higher in vitro therapeutic index. Thus, we investigated the synthesis and antiviral activities of various quercetin derivatives with substitution of C3, C30 , and C5 hydroxyl functions with various phenolic ester, alkoxy, and aminoalkoxy moieties. Among newly synthesized compounds, quercetin- 3-gallate which is structurally related to EGCG showed comparable antiviral activity against influenza virus (porcine H1N1 strain) to that of EGCG with improved in vitro therapeutic index.
Keywords: Antiviral activity; Influenza virus; Porcine H1N1 strain; Quercetin-3-gallate; Substituted quercetins